Empowering Youth through Buddhist Education - Singh, Arvind Kumar (The Journal of International Association of Buddhist Universities (JIABU), 2018)
This paper focus is on how we can empower youth through Buddhist education. It looks at some of the environmental factors and external pressures that the youth of today have succumbed too. It looks to proves that not only that the empowerment of youth is possible through Buddhist education; it also proposes that thought the empowerment of the youth, peace in society is a very tangible goal. The researcher has identified and given a brief synopsis of numerous Buddhist Sutta that he believes are most suited to the empowerment of today’s youth.